Avaliação da dinâmica do uso da terra na bacia do arroio Santa Bárbara - pelotas (Brasil), no período de 1953 a 2006 - Simon, Adriano Luís Heck [UNESP]; Trentin, Gracieli; da Cunha, Cenira Maria Lupinacci [UNESP] (My University, 2010)
Land use dynamics is a consequence of socioeconomic system cycles. In this context, this work was developed aiming to evaluate land use alterations in Santa Bárbara watershed (Pelotas - Brazil), during 53 years (1953 - 2006), evidencing socioeconomic elements that contributed to this process. For land use dynamic analysis, maps of 1953, 1965, 1995 e 2006 were elaborated. Spatial changes that happened in Santa Bárbara watershed represent a regional process: pasture areas had decrease while culture lands had a gradual increase. This conjuncture is a consequence of the crisis in livestock destined to salted and dried meat production and of the food industry growth in Pelotas that impelled urban expansion, forest area reduction and artificial water reservoirs increase. © Scripta Nova, 2010.
Land use evaluation in Santa Bárbara watershed - pelotas (Brazil) from 1953 to 2006
Keywords: Land use dynamic; Pelotas (Brazil); Rural space changes; Socioeconomic cycles; Urban expansion